New results in strip Kalman filtering - Azimi-Sadjadi, Mahmood R., author; IEEE, publisher (Colorado State University. Libraries, 1989)
The strip Kalman filtering proposed in [1] for image restoration is reconsidered. The procedure given in this reference for parameter estimation of the image model does not take into account the vector nature of the image process, and as a result can lead to incorrect identification. It is also shown that for the composite dynamic model derived in this reference the standard Kalman filtering equations cannot be applied, as the blur states in this model should be estimated one step ahead. These issues are addressed in this paper.
Keywords: picture processing; parameter estimation; Kalman filters; filtering and prediction theory